HYPERHOMOCYSTEINEMIA AS A RISK FACTOR FOR THE DEVELOPMENT OF PATHOLOGICAL CHANGES IN THE CARDIOVASCULAR SYSTEM: MECHANISMS AND CONSEQUENCES - Todorović, Dušan; Stojanović, Marija; Djuric, Dragan (Medicinski podmladak, 2023)
Hyperhomocysteinemia represents a pathological condition characterized by an increased concentration of homocysteine in the blood, exceeding the threshold of 15 µmol/L. Hyperhomocysteinemia can be caused by genetic defects in enzymes involved in the metabolism of homocysteine and inadequate intake of vitamin B6, folic acid, and/or vitamin B12, disturbances in kidney and thyroid function, malignant diseases, psoriasis, and diabetes, as well as the use of certain medications, alcohol, tobacco, and caffeine. Hyperhomocysteinemia leads to damage to blood vessels through the induction of the proliferation of vascular smooth muscle cells, disruption of physiological endothelial functions, accumulation of reactive oxygen and nitrogen species, i.e., induction of oxidative and nitrosative stress, increased production of collagen, and degradation of the elastic fibers of the arterial wall, disturbance in the production of nitric oxide, dysfunction in the H2S signaling pathway, cellular hypomethylation, homocysteinylation of proteins, and disturbances in lipid metabolism. These pathophysiological mechanisms lead to accelerated atherosclerosis, which ultimately results in diseases such as acute myocardial infarction, heart failure, stroke, and peripheral vascular disease. In patients with the aforementioned diseases, or with associated risk factors such as hypertension, diabetes, obesity, smoking, or a positive family history of coronary heart disease, it is of great importance to determine and monitor the concentration of homocysteine in the blood and to take measures in the form of lifestyle changes aimed at secondary prevention of the consequences that hyperhomocysteinemia brings with it.
Keywords: homocysteine; hyperhomocysteinemia; cardiovascular system; endothelial dysfunction; atherosclerosis